(untitled) (Fiep Bulletin - online, 2013)
This study aims at comparing the answers of three social groups dealing with themes related with organ donation and the transplants law in order to know whether there is divergence among them. The sample consisted of 25 students at the 7th level of the course of medicine at UFPB, 25 students at the 3rd level of the course of Law at UFPB and an evangelizing group of 25 people of a church in the fishermen’s villa in the city of João Pessoa-PB. The research was accomplished from December 2006 to February 2007. The data collection consisted of a questionnaire applied to the three groups. The questionnaire contained data dealing with age, sex, group and six closed and open questions on the theme. For the analysis of the quantitative data the Chi-square test was applied with the level of significance at 5% and for the justifications of the answers of the undecided informants, the technique of content analysis was used. It was observed that the groups are homogeneous in four of the six surveys, i.e., there was only difference statistics in two. The significant difference was observed in the answer on reliability in the diagnosis of encephalic death, 64% of the% Students of medicine Students of law p-value = 0,047744 Proportion of affirmative answer Comparison between the groups (% of affirmative answers) Fishermenÿs villa (%) students of medicine (%) students of law (%) p-value Would you donate an organ? 72 76 68 0,82003 For the fact that anyone can be a donor, does it favor the trade of organs? 68 76 64 0,70238 Do you find the unique list of receptors reliable ? 8 20 4 0,11886 Once the patient with encephalic death is a potential donor, do you rely on a diagnosis of such death type? Does the organ transplant law respect the human dignity? 40 28 48 0,49935 Would you donate organs in life? 84 84 72 0,47237 FIEP BULLETIN Volume 79 - Special Edition - ARTICLE I - 2009 students of medicine at the 7th level at UFPB trust this diagnosis, the evangelizing group of the fishermen’s villa versus 12%. The other difference lied in the answer on the reliability in the receptors unique list, 36% of the students of the 7th level at UFPB affirmed to trust the list; the students of Law of the 3rd level at UFPB versus 12% .This difference was only observed when the exact test of Fisher was applies. It is concluded that among the informants, due to their belonging to three different social groups of different characteristics, there was no identification of knowledge estrangement about the issues on the theme " organ donation ", being thus demonstrated that all of them have the same opinion in four of the six surveys.